2012
DOI: 10.1182/blood-2012-02-413286
|View full text |Cite
|
Sign up to set email alerts
|

HCV glycoprotein E2 is a novel BDCA-2 ligand and acts as an inhibitor of IFN production by plasmacytoid dendritic cells

Abstract: IntroductionThe eradication of hepatitis C virus (HCV) in Ͼ 50% of chronically infected patients by treatment with IFN-␣ 1,2 suggests that production of endogenous IFN-␣ plays an important role in the control of HCV infection. Plasmacytoid dendritic cells (pDCs) are a highly specialized subset of dendritic cells that function as sentinels for viral infection and are responsible for production of type I (IFN-␣ and ␤) and type III (IFN-/IL-28/29) IFNs, proinflammatory cytokines, and antigen presentation during v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 35 publications
3
55
0
1
Order By: Relevance
“…Viruses can highjack the signaling pathways downstream of such receptors and escape from immune recognition (Figure 2). For example, the hepatitis C virus (HCV) envelope glycoprotein E2 binds to BDCA2 and DCIR, which inhibits IFNα production in pDC when exposed to HCV-infected hepatocytes(23). Moreover, exposure of pDC to HCV-infected hepatoma cells prevents NFκB phosphorylation via an endocytosis-dependent mechanism resulting in a lack of cell surface expression of CD40, CCR7, CD86 and TRAIL, and of TNFα and IL6 secretion(24).…”
Section: Counter Regulation Of Tlr Signalingmentioning
confidence: 99%
“…Viruses can highjack the signaling pathways downstream of such receptors and escape from immune recognition (Figure 2). For example, the hepatitis C virus (HCV) envelope glycoprotein E2 binds to BDCA2 and DCIR, which inhibits IFNα production in pDC when exposed to HCV-infected hepatocytes(23). Moreover, exposure of pDC to HCV-infected hepatoma cells prevents NFκB phosphorylation via an endocytosis-dependent mechanism resulting in a lack of cell surface expression of CD40, CCR7, CD86 and TRAIL, and of TNFα and IL6 secretion(24).…”
Section: Counter Regulation Of Tlr Signalingmentioning
confidence: 99%
“…Similarly, activation of either human BDCA-2 or murine Siglec H induces an inhibitory signal through spleen tyrosine kinase (Syk) to attenuate IFN-I production [81]. A recent report found that hepatitis C viral glycoprotein e2 ligates BDCA-2 to inhibit pDC production of IFN-I and III [82], while elevated phosphorylation of Syk is associated with attenuated IFN-I production by HIV-stimulated pDCs [83]. It will be important to determine whether respiratory viruses, and in particular those associated with the onset of asthma, are able to engage BDCA-2 or ILT7 to evoke inhibitory signals that suppress IFN-I release.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pDCs were reported to not express the cell surface proteins CD40, CD86, CCR7 and TRAIL [64]. HCV E2 protein can bind pDC-specific type II C-type lectin (BDCA) and DC immunoreceptor (DCIR) and inhibit TLR7 and TLR9-mediated IFN-a or IFN-l release by pDCs [65]. Furthermore, mDCs of CHC patients show elevated expression of Fas ligand and PD-L2 compared with those from healthy controls, and have cytotoxic effects on both autologous and heterologous T cells.…”
Section: Hepatitis C Virus and Hepatitis B Virusmentioning
confidence: 99%